2014
DOI: 10.5799/ahinjs.02.2014.s1.0138
|View full text |Cite
|
Sign up to set email alerts
|

Overview of West Nile Virus and Sandfly-borne Phlebovirus Infections in Anatolia

Abstract: Arthropod-borne (arbo) viruses are trafinsmitted to the susceptible hosts by blood-feeding arthropods such as mosquitoes, sandflies and ticks. Arboviral infections have had a significant global public health impact during the last decades due to their resurgence and dynamic epidemiologic features. In Turkey, cases and outbreaks due to previously underestimated arboviral infections have emerged since 2009. In this manuscript, previous and current data on two of the major arboviral infections, West Nile virus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
3
0
3
Order By: Relevance
“…A detailed assessment of content in this cohort revealed that 2 reports were merely focusing on West Nile virus without presenting data on phleboviruses and were subsequently omitted . Review articles that present general or agent‐specific information on vector‐borne infections in Turkey including phleboviruses comprised 7 of the entries, and they were examined for further cited research on phleboviruses. Two reports presented surveillance data on the mosquito‐borne pathogenic phlebovirus Rift Valley fever virus, where serological and nucleic acid tests gave negative results in 350 sera (from cattle, horse, sheep, goat, and water buffaloes) and in aborted fetuses, collected from the Black Sea region of Turkey.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed assessment of content in this cohort revealed that 2 reports were merely focusing on West Nile virus without presenting data on phleboviruses and were subsequently omitted . Review articles that present general or agent‐specific information on vector‐borne infections in Turkey including phleboviruses comprised 7 of the entries, and they were examined for further cited research on phleboviruses. Two reports presented surveillance data on the mosquito‐borne pathogenic phlebovirus Rift Valley fever virus, where serological and nucleic acid tests gave negative results in 350 sera (from cattle, horse, sheep, goat, and water buffaloes) and in aborted fetuses, collected from the Black Sea region of Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1693 database entries that comprise 1491 (88.1%) international and 202 (11.9%) regional reports were accessed. Following the omission of repetitive and/or unrelated records, 42 manuscripts emerged . A detailed assessment of content in this cohort revealed that 2 reports were merely focusing on West Nile virus without presenting data on phleboviruses and were subsequently omitted .…”
Section: Resultsmentioning
confidence: 99%
“…Serosürveyans çalışmaları, olgu bazlı taramalar ve vektör taramalarına ek olarak, bölgede bulunan ve insan maruziyeti izlenen virusların saptanması ve epidemiyolojik özelliklerinin belirlenmesinde önem taşır 7,8 . Bu çalışmada, Mersin ili ve çevresinde yaşayan sağlıklı kan donörle- …”
Section: Discussionunclassified
“…Bununla birlikte ülkemizde fl ebovirus enfeksiyonlarına ait veriler görece olarak kısıtlıdır 7 . Özellikle son beş yılda olgu sunumları ve sürveyans verileri, TOSV ve SFTV de dahil olmak üzere, çeşitli fl eboviruslara, klinik hastalıkla sonuçlanan ya da sonuçlanmayan maruziyetin sıklıkla ortaya çıktığını göstermektedir 8 . Bu çalışmada, Akdeniz bölgesi kıyısında yer alan bölgemizde çeşitli fl eboviruslara maruziyetin serolojik yöntemlerle araştırılması amaçlanmıştır.…”
Section: Introductionunclassified
“…Ülkemizde son on yıl içinde Akdeniz bölgesi ve Orta Anadolu'da SFV'ye bağlı olgular ve salgınlar bildirilmiştir [6][7][8] . Klinik belirti ve bulgular spesifik olmayıp ancak akla getirilirse tanısı netleşmektedir.…”
Section: Introductionunclassified